Clinical significance of anti-glycopeptidolipid-core IgA antibodies in patients newly diagnosed with Mycobacterium avium complex lung disease. (September 2020) - Matsuda, Shuichi; Asakura, Takanori; Morimoto, Kozo; Suzuki, Shoji; Fujiwara, Keiji; Furuuchi, Koji; Osawa, Takeshi; Namkoong, Ho; Ishii, Makoto; Kurashima, Atsuyuki; Tatsumi, Koichiro; Ohta, Ken; et al.
Abstract: Background: Although recent studies have identified anti-glycopeptidolipid (GPL)-core IgA antibodies as a serodiagnostic test for Mycobacterium avium complex lung disease (MAC-LD), this test shows insufficient sensitivity. This study aimed to determine the clinical utility of these antibodies in assessing disease progression and the clinical characteristics of MAC-LD patients with negative antibody results. Methods: We retrospectively reviewed the medical records of consecutive newly diagnosed, untreated MAC-LD patients in two referral hospitals. We evaluated the association of anti-GPL-core IgA antibody results with disease progression requiring treatment and the factors associated with negative antibody results. Results: In total, 229 patients (161 females; median age, 71 years; 185 with nodular/bronchiectatic disease phenotype; 69 with cavitary lesions) were enrolled; 146 patients (64%) were anti-GPL-core IgA antibody-positive. Radiological severity scores were associated with anti-GPL-core IgA antibody titers. During the median 364-day follow-up, 114 patients (49.8%) required treatment. Multivariate Cox proportional hazards analysis showed that positive anti-GPL-core IgA antibody results, a younger age, the absence of malignancy, and the presence of cavitary lesions were associated with disease progression requiring treatment. Multivariate logistic analysis revealed that significant factors related to the negative antibody results included underlying pulmonary disease, lower radiological scores, chronic sinusitis, and macrolide monotherapy. Conclusion: In addition to cavitary lesions, anti-GPL-core IgA antibody positivity was associated with disease progression requiring treatment. Physicians should carefully use anti-GPL-core IgA antibody results for the diagnosis of patients with underlying pulmonary disease, chronic sinusitis, macrolide monotherapy, and lower radiological severity. Highlights: The presence of cavitary lesions is associated with MAC-LD progression. Anti-GPL-core IgA antibody positivity may also help predict disease progression. However, this antibody should be used, considering the causes of false-negatives.